Fine particle deposition to initially starved, stationary, planar beds - HAMM, NATHAN T; DADE, W. BRIAN; RENSHAW, CARL E (Sedimentology, 2009)
Reported here are results from new flume experiments examining deposition and entrainment of inert, silt-sized particles (with spherical diameters in the range from 20 to 60 μm) to and from planar, impermeable and initially starved beds underlying channel flows. Bed surfaces comprised smooth or fixed sand-size granular roughness and provided hydraulically smooth to transitionally rough boundaries. Results of these experiments were analysed with a simple model that describes the evolution of vertically averaged concentration of suspended sediment and accommodates the simultaneous delivery to and entrainment of grains from the bed. The rate of particle arrival to a bed diminishes linearly, and the rate of particle entrainment increases by the 5/2 power, as the value of the dimensionless Saffman parameter S = u*³/g'ν approaches a threshold value of order unity, where u* is the conventional friction velocity of the turbulent channel flow, g' is the acceleration due to gravity adjusted for the submerged buoyancy of individual particles and ν is the kinematic viscosity of the transporting fluid. This transport behaviour is consistent with the notion that non-cohesive, silt-sized particles can neither reach nor remain on an impermeable bed under flow conditions where mean lift imposed on stationary particles in the viscous sublayer equals or exceeds the submerged weight of individual particles. Within the size range of particles used in these experiments, particle size and the characteristic size of granular roughness, up to that of medium sand, did not affect rates of dimensionless arrival or entrainment to a significant degree. Instead, a new but consistent picture of fine-particle transport is emerging. Silt-sized material, at least, is subject to potentially significant interaction with the bed during intermittent suspension transport at intermediate flow speeds greater than the value required for initiation of transport (ca 20 cm sec⁻¹) but less than the value (ca 50 cm sec⁻¹) required by the Saffman criterion ensuring transport in fully passive suspension or, equivalently, 'wash-load'.